PKM Empowerment and Mentoring Cooperation Contracts at The Bali Dance Sanggar Dewi Ratih Banjar Busana Kaja, Baha Village, Mengwi District, Badung District - Desak Gde Dwi Arini; Ni Made Sukaryati Karma; Ni Ketut Sukiani (Fakultas Hukum, Universitas Warmadewa, 2024)
Community service activities are carried out at the Dewi Ratih Bali Dance Studio in Banjar Busana Kaja, Baha Village, Mengwi District, Badung Regency, activities are carried out by providing legal consultation and assistance to the Dewi Ratih dance studio in the field of cooperation contracts and various areas of life in the field of empowering the Balinese dance studio. Dewi Ratih, as well as legal protection for the Dewi Ratih Bali Dance Studio at Banjar Busana Kaja, Baha Village, Mengwi District, Badung Regency, provides very important assistance to maintain the existence of an art studio and ensure that its work is not claimed by other parties. With the operational permit issued for the Dewi Ratih Busana Kaja Dance Studio in 2019, therefore, through the community partnership program, the PKM Team, Faculty of Law, Warmadewa University, Denpasar carried out assistance in drafting cooperation agreements with other parties. This aims to have legal certainty by having authentic evidence that the Bali Dewi Ratih dance studio has officially become an organizational association with a legal entity. With proof of the legality of the Balinese dance studio, it will become a legal umbrella for the people of Indonesia as an Art Culture, especially Banjar Busana Kaja, Baha Village, Mengwi District, Badung Regency, so that there are no other Balinese dance studios with the same name, because this is not the case. permitted by law. Apart from that, as an organization that is a legal entity, the Balinese dance studio Dewi Ratih at Banjar Busana Kaja has clear rights and obligations as a legal subject, which will later have the right to receive cooperation with other parties and grant programs from both the private sector and the government. The legality of a studio that has become a legal entity opens up opportunities for PKM partners to be able to more freely preserve local culture because its legality is guaranteed and has the potential to receive guidance and grant assistance from the government and the private sector. Likewise, empowerment for the preservation of Balinese dance at Sanggar Dewi Ratih continues to be optimally improved, by maximizing the number of students at the Dewi Ratih Studio, not only the dance members are female in accordance with the name of the Dewi Ratih Studio, but it is also hoped that the dance members will be male so they can collaborate in the field of dance. , and always promote Balinese dance studios not only through offline media but also through online media with the aim of ensuring that Balinese dance culture does not become extinct and continues from generation to generation. In fact, the existence of Balinese dance culture continues to exist. Increasing the renewal of Balinese dance art creations and collaborating with other cultures to make them more varied and more creative. The empowerment and preservation of Balinese dance studios is always optimized and improved when tourists visit and government guests visit Baha Village as a tourist attraction area and it is always performed during religious ceremonies.